Technical Note: Correction for intra‐chamber dose gradients in reference dosimetry of flattening‐filter‐free MV photon beams. Issue 8 (21st July 2016) - Ruggieri, Ruggero; Naccarato, Stefania; Stavrev, Pavel; Stavreva, Nadejda; Pasetto, Stefano; Salamone, Ignazio; Alongi, Filippo
Abstract : Purpose: To estimate and correct for the volume averaging effect which results from the intra‐chamber dose gradients when a Farmer ionization chamber (IC) is used for reference dosimetry in flattening‐filter‐free (FFF) MV photon beams. Methods: An intra‐chamber dose gradients correction factor ( k icdg ) to the charge reading of a Farmer IC is estimated by comparison to a small volume IC (∼0.1 cm 3 ), in the FFF beams of a TrueBeam™ (Varian, Inc.) linear accelerators. An independent estimate of the correction for the volume averaging effect ( p vol ) is deduced using the ratio of the active length ( L ) of the Farmer IC to the integral of a high‐resolution FFF radial dose profile over this same length. Results: Mean (sd) values for k icdg equal to 1.0025 (0.0025) for 6 MV‐FFF, and equal to 1.0057 (0.0025) for 10 MV‐FFF, were estimated based on four dosimetry sessions, performed in a time interval of six months. Similarly, p vol Farmer equal to 1.0030 (0.0003) for 6 MV‐FFF, and equal to 1.0063 (0.0005) for 10 MV‐FFF, were computed. Conclusions: The systematic bias which results from intra‐chamber dose gradients when a Farmer IC is used for reference dosimetry in FFF MV photon beams is estimated to be −0.6% for 10 MV‐FFF, and −0.3% for 6 MV‐FFF, based on the obtained values of the factor k icdg . This bias can be corrected, within 0.1%, by the simple measure of p vol at the beginning of the dosimetry session.